Potential Hematopoietic Effects of SGLT2 Inhibitors in Patients with Cardiac Amyloidosis - Nikita Ermolaev; Robin Willixhofer; Christoph Krall; Christina Kronberger; René Rettl; Christina Binder; Franz Duca; Christian Nitsche; Andreas Kammerlander; Michael Poledniczek; Bernhard Gregshammer; Diana Ahmadi-Fazel; et al. (Reviews in Cardiovascular Medicine)
Background: Sodium–glucose cotransporter 2 inhibitors (SGLT2i) have been found to have potential hematopoietic effects in patients with heart failure (HF). However, these benefits have not been studied in patients with cardiac amyloidosis (CA). CA patients present with HF symptoms and often suffer from iron deficiency, which has a negative impact on erythropoiesis and leads to lower hemoglobin and hematocrit levels. We sought to determine the potential effects of SGLT2i on hematological parameters and functional capacity (FC) in CA patients. Methods: A prospective analysis was conducted to compare the effects of SGLT2i in patients who received the best medical therapy (BMT) along with SGLT2i (n = 20), versus patients receiving only BMT without SGLT2i (n = 20) (historical control group). All patients underwent blood testing and cardiopulmonary exercise testing (CPET) at baseline (BL) and after 6 months [interquartile range (IQR): 4.0 to 8.0]. Results: The SGLT2i-based therapy resulted in a significant improvement and difference in hematological parameters at 6 months follow-up compared to the control group. In the SGLT2i group, the mean hemoglobin level increased (+1.2 mg/dL), whereas in the control group, it decreased (–0.8 g/dL) (p < 0.001 for overall group comparison). The hematocrit showed a significant increase in the SGLT2i group (+4.4%) compared to a decrease in the control group (–1.8%) (p < 0.001). Additionally, the serum iron level improved in the SGLT2i-treated group (+ 5.5 [–5.0 to 17.5] μg/dL vs. –6.0 [–15.0 to 4.0] μg/dL, p = 0.121). Although there was no significant change in the peak oxygen consumption (peak VO2, (mL/min)/kg) (p = 0.206), as well as in pulmonary ventilation (VE)/carbon dioxide production (VCO2) slope in both groups (p = 0.964), the SGLT2i group maintained a peak VO2 and VE/VCO2 slope throughout the study. Conclusions: SGLT2i therapy improved hematological parameters and stabilized the FC of CA patients.